PENERJEMAH, PENERJEMAHAN, TERJEMAHAN, DAN DINAMIKA BUDAYA: MENATAP PERAN PENERJEMAHAN PADA MASA LALU DI NUSANTARA - Hoed, Benny H. (Masyarakat Indonesia, 2011)
This paper describes the role and impact of translation on cultural change. Translation is defned as an effort to divert messages from one language (source language) into another language (target language). Language, through translation and transfer of messages, can affect the formation of the target culture as stated in the “Sapir-Whorf hypothesis”. Many studies on translation are generally talking about the quality of translation. This paper however does not discuss about quality of the translation instead it focuses on the role of translation and its impact on target communities. Specifcally, it talks about the subject of the translation and the translation in the beginning of Hinduism and Islamic period and the New Order period in Indonesia. The paper observes the translation from the perspective of “its purpose”, which is known as “skopos method.” It reviews four articles contained in the book ofSadur. The paper also shows how the translation may have an impact on cultural change, i.e. how the translators introduce, distribute, or take advantage of cultural elements contained in the source text while adjusting to the needs of target communities. The main purpose of those translations studied is to spread the religion, literature, and social rules. There are three things observed through translation: (i) the role of the source language as the language of religion, administration, and literature is taken over by the target language. (ii) the genre of the source language is replaced with the genre of the target language. (iii) teaching of Hinduism and Islam were inserted into local religious teachings; literary sources adapted to local literature. The paper concludes that “the Sapir-Whorf hypothesis” applies where the translation shapes culture. And translation, based on the principle of “sadur” (adaptation) and “pemribumian” (domestication), has formed “a new fgure” of local culture in the history of Indonesia.